PENGETAHUAN IBU MERUPAKAN FAKTOR RISIKO GIZI BURUK PADA ANAK USIA 6-59 BULAN DI DAERAH PESISIR KOTA KENDARI - Juminten Saimin; Ahmad Fahmi Nugraha; Ashaeryanto Ashaeryanto; Asmarani Asmarani (Berita Kedokteran Masyarakat (BKM), 2020)
Objective: To determine the effect of mother’s knowledge on the incidence of malnutrition in children aged 6-59 months in the coastal areas of Kendari.Method: This was a case control study conducted in the coastal area of Kendari in November to December 2018. Cases were children aged 6-59 months with malnutrition, while controls were children with good nutrition. The data was obtained from the medical records of Abeli, Mata and Benu-Benua Health Center from January to October 2018. Malnutrition was determined by Z-score (body weight/age). A total of 16 cases were taken with total sampling and 48 controls were taken with purposive sampling with non-matching method according to the inclusion and exclusion criteria. Mother's knowledge was determined using the modification questionnaire. Data analysis with statistical tests assessing Odd Ratio (OR), with a 2x2 contingency table and a 95% confidence level with a significance level of α = 0.05. This study was approved by the Medical and Health Research Ethics Commission of Halu Oleo University.Results: Most cases of malnutrition were aged 25-48 months. The majority of respondents aged 20-35 years old, consisting of cases (50,0%) and controls (64,6%). The majority of maternal education levels were primary education in the case group (75,0%) and secondary education in the control group (47.9%). The majority of the case groups had less knowledge (81.3%) while the control group had good knowledge (68.7%). Statistical test results obtained OR = 9.533 (CI=95%) with Lower Limit (2.361) and Upper Limit (38.501). Conclusion: Mother’s knowledge is a risk factor for malnutrition in children aged 6-59 months in the coastal areas of Kendari. Mothers with less nutritional knowledge are at 9 times the risk of having children with poor nutrition. A counseling program is needed to improve maternal nutrition knowledge.Keywords: children, coastal areas, malnutrition, mother’s knowledge